(untitled) (Comparative & International Education Series, 2021)
In a rapidly changing economic context, students across the globe graduate from post-secondary institutions lacking the skills needed to transition into a evolving labor market. In many countries, post-secondary education focuses on theory and is divorced from market realities. This chapter will provide insights on how educational institutions and systems can respond to demands of employers, instructors, and students, resulting in better employment and entrepreneurship outcomes. It will examine three innovative interventions: • Bringing industry into the classroom to work directly with youth (Indonesia and Thailand); • Supporting instructor professional development to introduce project-based activities that promote work-readiness and technical skills (SE Asia); and • Cultivating an entrepreneurial mindset and career ownership in recent university graduates, while up-skilling and re-training them for opportunities in high growth industries (Senegal). We will identify how these strategies are fully owned and sustained by local institutions, and analyze their impact in successfully addressing the skills gaps.